Low-density conductive adhesive applied to photovoltaic imbricate assembly and preparation method of low-density conductive adhesive
By using silver-coated plastic particles and adjusting the curing agent combination in the stacked tiles, low-density and high flexibility conductive adhesives are achieved, and the explosive accumulation problem of conductive adhesives in the existing technology during the high-temperature curing process is solved. Reduces cost and component weight, improves reliability and market competitiveness.
Patent Information
- Application Number
- CN202411533966.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
The existing stacked conductive glue is prone to bursting during the rapid curing process of high temperature, resulting in bubbles and holes, affecting the aging reliability of the battery cells. At the same time, it is costly and has too much dependence on silver powder, affecting market competitiveness.
Using a low-density conductive adhesive formula containing silver-coated plastic particles, the combination of curing agent and filler can achieve short-term rapid curing under medium and high temperature conditions, reduce the amount of conductive adhesive, control the height of the glue layer, reduce the modulus, and improve the Component reliability.
It realizes low density and high flexibility of conductive adhesives, reduces production costs, improves the mechanical load and reliability of components, reduces component weight, and enhances market competitiveness.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to conductive adhesive, in particular to a low-density conductive adhesive applied to photovoltaic shingled components. Background Art
[0002] Solar energy is gaining more and more attention due to its advantages such as being pollution-free, inexhaustible, and not limited by geographical resources. A solar cell is a semiconductor electrical device that directly converts solar energy into electrical energy through the photoelectric conversion effect. Under light conditions, solar cells generate current, which is collected and transmitted through grid lines and electrodes.
[0003] Among the many types of solar cell modules, shingled solar cell modules are an important development direction of high-efficiency solar cell module technology. Shingled modules use laser to cut solar cells into several pieces and then connect them with conductive glue. By eliminating the gap between cells, the effective cell capacity of the module is increased. Shingled modules have higher module power than traditional ribbon welding modules.
[0004] Conductive adhesive is a key material to achieve current conduction connection of each shingled cell. The temperature of traditional soldering of cells is above 300℃. When the cells are welded, huge thermal stress is instantly generated on the front and back sides, causing serious bending of the cells, and even causing hidden cracks and fragmentation of the cells, thereby reducing the yield and increasing the cost. Conductive adhesive has the characteristics of low-temperature curing, good flexibility, and bonding without generating too much stress. It is an effective way to solve the problem of hidden cracks and thermal stress of cells.
[0005] As a bonding material, the conductive adhesive also plays the role of buffering the thermal stress and tensile force during the actual operation of the shingled assembly. Well-designed conductive adhesive can greatly improve the reliability performance of the shingled assembly.
[0006] The height of the conductive adhesive layer is one of the important factors affecting the reliability of shingled modules. A higher conductive adhesive layer has a very weak effect on module power, but a very important effect on module reliability. The higher the adhesive height, the better the stress buffering between cells. At the same time, the shingled cell string has a higher tolerance to bending deformation, and the power attenuation is also less in mechanical load tests and thermal cycle tests. How to control the height of the conductive adhesive layer places very high demands on the manufacturing process of shingled modules.
[0007] Existing shingled conductive adhesives are mainly based on three bonding technologies: one-component epoxy resin, one-component silicone resin and one-component acrylic resin. The main advantages of epoxy adhesives are high bonding strength, but long curing time, low process efficiency, high modulus, high brittleness, and easy cracking of the adhesive layer under hot and cold shock conditions with strong loads; one-component silicone resin has good flexibility and low internal stress after curing, but low bonding strength; one-component acrylic resin has fast curing speed and high bonding strength, but it also has strong rigidity, high modulus, and easy cracking of the adhesive layer under hot and cold shock conditions, causing module failure and other problems. Continuously reducing costs is one of the important goals of the development of the solar cell industry. At present, the shingled conductive adhesives on the market all use silver powder as the conductive filler, and the silver content is mostly 70-80%. The high cost of raw materials also affects the market competitiveness of shingled components.
[0008] Patent application CN202410278194.5 discloses a low-density conductive adhesive that cures at medium and low temperatures, as well as its preparation method and application, comprising the following components in parts by weight: 10 to 20 parts of epoxy resin A; 5 to 10 parts of epoxy resin B; 1 to 5 parts of epoxy resin C; 0.1 to 5 parts of latent curing agent D; 0.1 to 1 part of latent curing agent E; 0.1 to 0.5 parts of coupling agent; 20 to 40 parts of lightweight conductive filler F; and 10 to 50 parts of conductive filler G. Using silver-coated non-metallic particles as fillers reduces the density of the conductive adhesive, adjusts the modulus and toughening method of the colloid, and thus improves the device's ability to resist falling, which is beneficial to improving the reliability of the device. However, due to the low curing temperature range of the curing agent, when high-temperature rapid curing is used in the shingling process, it is very easy to produce implosion, which in turn produces a large number of bubbles and holes, affecting the aging reliability of the battery cell; in addition, the shingled components are often made into curved structures during the design process, and will be subjected to continuous thermal stress and tensile force during actual operation, which has higher requirements for the flexibility of the conductive adhesive and a correspondingly lower modulus. Finally, the shingled conductive adhesive is more sensitive to cost, and the difference of a few milligrams in a single glue point will be a very considerable benefit when the installed capacity is accumulated to GW. Summary of the invention
[0009] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a low-density conductive adhesive for use in photovoltaic shingled modules and a preparation method thereof, which can achieve rapid curing in a short time under medium and high temperature conditions, reduce the amount of conductive adhesive used, effectively control the height of the shingled adhesive layer, reduce the modulus of the conductive adhesive, and improve the reliability of the module.
[0010] The object of the present invention can be achieved by the following technical solution: A low-density conductive adhesive applied to a photovoltaic shingled assembly comprises the following components in parts by weight:
[0011] Epoxy resin A 10-20 parts;
[0012] Epoxy resin B 5-15 parts;
[0013] Epoxy resin C 3-10 parts;
[0014] Curing agent D 0.1-2 parts;
[0015] Curing agent E 0.1-2 parts;
[0016] Curing agent F1 to 5 parts;
[0017] 0.1-0.5 parts of coupling agent;
[0018] Conductive filler G 40-70 parts.
[0019] Furthermore, the epoxy resin A is a multifunctional phenolic epoxy resin with a viscosity of 2500-6500 Pa·s at 25°C, an average functionality of 2.2, an epoxy equivalent of 172-179 g / eq, and a total chlorine content of <1000 ppm. Epoxy resin A can provide high crosslinking density, high adhesion, low water absorption, and high reliability. One or more of N-730A from DIC of Japan, NPPN-631 from Nan Ya Plastics Industry Co., Ltd., YDPN-631 and YDPN-638 from Kukdu Chemical Co., Ltd., and EPN 9850 from Huntsman can be selected.
[0020] Furthermore, the epoxy resin B is a silicone-modified epoxy resin with a viscosity of 30 to 60 Pa·s at 25°C, an epoxy equivalent of 750 to 900 g / eq, and a density of 0.99 to 1.05 g / cm at 23°C. 3 You can choose one or more of ALBIFLEX 246, ALBIFLEX 296, ALBIFLEX 297 from Evonik, KHE-8000H from Nippon Kayaku, SEI-7030, SEI-8030 from Selvi New Materials.
[0021] Furthermore, the epoxy resin C is a high-purity, low-viscosity, bifunctional non-crystalline epoxy resin with a viscosity of 2-3 Pa·s at 25°C, an epoxy equivalent of 160-170 g / eq, and a total chlorine content of <800 ppm. One or more of the epoxy resins can be selected: ZX-1059 from Nippon Steel Corporation of Japan, EPICLON 835LVP from DIC of Japan, JE-8672H from Jiadida Chemical, and ZLX-165H from Zhilun New Materials.
[0022] Furthermore, the curing agent D is imidazole, a light yellow liquid, with a molecular weight of 163.22, a purity of 98.0%, and is soluble in ethanol, acetone, and benzene. 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-ethyl-4-methylimidazole, ADEKA's EH-2021, Shikoku Chemical's 1B2MZ, 1B2PZ, etc. can be selected.
[0023] Furthermore, the curing agent E is a latent curing agent with a core-shell structure, which can achieve stable storage at room temperature and rapid curing under corresponding temperature conditions. HX-3941HP, HX-3921HP, HXA3932HP, etc. of Asahi Chemical Co., Ltd. of Japan can be selected. Preferably, HXA3922HP and commercially available bisphenol A epoxy resin, such as EPICLON 840, EPICLON 850, EPICLON 850CRP, etc. (epoxy equivalent EEW: 168-195 g / eq) of DIC are used in a weight ratio of 30:100, with a gel time of 1 minute at 130°C and a gel time of less than 1 minute at 170°C. The average particle size is 2 μm, the viscosity is 70-200 Pa·s, and the total chlorine is <1000 ppm.
[0024] Furthermore, the curing agent F is a latent solid powder. 2P4MZ, 2P4MHZ, 2P4MHZ-PW from Shikoku Chemical Co., Ltd.; OMICURE DDA 5, OMICURE DDA 10 from CVC; PN-40J, PN-50 from Ajinomoto Co., Ltd., etc. can be selected. 2P4MHZ-PW from Shikoku Chemical Co., Ltd. is preferred, with an average particle size of 5 μm, a molecular weight of 188.23, and a melting point of 192-197°C.
[0025] Furthermore, the coupling agent can be one or more of Z-6040, A-186, A-174, KH-550, KH-560, KBM-403, KBE-402, and KBE-403.
[0026] Further, the conductive filler G is: silver; nickel; carbon; carbon black; graphite; graphene; copper; gold; platinum; aluminum; iron; zinc; cobalt; lead; tin alloy; silver-coated nickel; silver-coated copper; silver-coated graphite; silver-coated aluminum; silver-coated glass; silver-coated plastic; nickel-coated graphite; and mixtures thereof. The conductive filler is generally pure silver powder with an average particle size of 2 to 7 μm and a specific surface area of 0.28 to 2.4 m 2 / g, tap density 1.4~5.2g / cm 3 ; Available products include Metalor's EA-0101, SA-0201, EA-0295, etc.; AgF-6A, AgF-3A, AgF-8A, etc. In order to reduce cost and density, silver-coated non-metallic particles are preferred, with an average particle size of 4μm to 30μm and a density of 1.4 to 2.9g / cm 3 The material of non-metallic particles is ABS, acrylic resin, methacrylic resin or glass. You can choose Conpart's Ag-4-1, Ag-10-3, Ag-20-02, etc.; Potters' S3000-S3E, S4000-S3, S5000-S3, etc.
[0027] The present invention also provides a low-density conductive adhesive for use in photovoltaic shingled modules. Epoxy resin A, epoxy resin B, epoxy resin C, curing agent D, curing agent E, curing agent F, coupling agent, and conductive filler G are weighed according to the formula ratio and put into a planetary mixer for stirring, and then vacuum degassing and stirring are performed to finally obtain the low-density conductive adhesive.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) Compared with traditional solder strips, the present invention has no lead pollution, has a low curing and bonding temperature, can reduce energy consumption, and reduces damage to solar cells.
[0030] (2) Compared with the existing conductive glue, the present invention uses silver-coated plastic particles as conductive fillers, and the colloid density is increased from 3.5g / cm 3 Around, greatly reduced to 2.5g / cm 3 According to the cell shingling process, the weight of the colloid can be greatly reduced under the condition of the same volume of colloid, thereby reducing the weight of the solar module and helping to achieve lightweighting of the entire solar panel.
[0031] (3) Compared with existing conductive adhesives, it significantly reduces the amount of precious metal fillers such as gold powder and silver powder, while maintaining the same level of volume resistivity. This is conducive to reducing costs and excessive dependence on silver powder, and promoting cost reduction and efficiency improvement in the solar energy industry.
[0032] (4) Compared with the existing epoxy conductive adhesive, the present invention uses a compound of curing agents with different temperature reaction activities. On the one hand, the curing temperature of the conductive adhesive is reduced, and the processing temperature is reduced from the previous 200°C to 160-180°C. At the same time, the curing speed is accelerated, and a curing rate of 95% can be achieved in only 3 minutes. The production energy consumption is effectively reduced and the production efficiency is improved; on the other hand, the operating time of the conductive adhesive is maintained at more than 16 hours, which meets the requirements of continuous operation of the shingling process.
[0033] (5) Compared with the existing conductive adhesive, the present invention adopts three different methods to adjust the modulus and flexibility of the conductive adhesive. First, the use of silicone-modified epoxy resin reduces the modulus of the conductive adhesive and increases the flexibility of the conductive adhesive, which is beneficial to the manufacture of shingled flexible components. Secondly, the use of silver-coated plastic particles as fillers significantly changes the volume ratio of organic and inorganic substances in the existing conductive adhesive system. At room temperature, the modulus of silver is between 10 and 22 GPa, while the modulus of plastic is between 0.1 and 4.0 GPa. Therefore, the use of silver-coated plastic particles to replace the silver powder in the existing conductive adhesive can also reduce the modulus of the colloid. Finally, the particle size of the silver-coated plastic particles is relatively small and is dispersed in the colloid during the preparation and curing process. When the conductive adhesive is cured and subjected to external force, it can hinder the propagation of cracks and play a toughening effect, thereby improving the tensile bending resistance of the component, which is beneficial to improving the mechanical load and reliability of the component. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The particle size distribution of silver-coated plastic particles Ag-4-1;
[0035] Figure 2 The particle size distribution of silver-coated plastic particles Ag-10-3;
[0036] Figure 3 This is the particle size distribution of silver-coated plastic particles Ag-20-02. DETAILED DESCRIPTION
[0037] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0038] The raw materials used in the present invention are all commercially available products unless otherwise specified. For example, the raw materials used in the following examples and comparative examples are
[0039] Epoxy resin A is epoxy resin N-730A produced by DIC Corporation of Japan.
[0040] Epoxy resin B is ALBIFLEX 296 epoxy resin produced by Evonik.
[0041] Epoxy resin C uses epoxy resin ZX-1059 produced by Nippon Steel Corporation of Japan.
[0042] The curing agent D is 1-cyanoethyl-2-ethyl-4-methylimidazole.
[0043] Curing agent E is HXA3922HP from Asahi Chemical Co., Ltd. of Japan.
[0044] The curing agent F is 2P4MHZ-PW produced by Shikoku Chemical.
[0045] The coupling agent used was Z-6040, a product originally from Dow Corning.
[0046] Conductive filler G uses silver-coated plastic particles Ag-4-1, Ag-10-3, Ag-20-02 from Conpart, pure silver powder EA-0101 and pure silver powder AgF-6A from Metalor.
[0047] Examples 1-3 and Comparative Examples 1-4
[0048] The weight proportions are as shown in Table 1.
[0049] Table 1 Formulas of Examples 1-3 and Comparative Examples 1-4 (parts by weight)
[0050]
[0051]
[0052] *Curing conditions: 180℃, constant temperature for 5 minutes.
[0053] According to the formula proportion in Table 1, epoxy resin A, epoxy resin B, epoxy resin C, curing agent D, curing agent E, curing agent F, coupling agent, and conductive filler G were weighed and put into a planetary mixer for stirring for 30 minutes, and then vacuum degassing and stirring for 30 minutes to finally obtain a low-density conductive adhesive.
[0054] The low-density conductive adhesives obtained in Examples 1-3 and Comparative Examples 1-4 were tested for performance according to corresponding standards.
[0055] Density testing method refers to "GB / T 13354-1992 Liquid Adhesive Density Determination Method Gravimetric Cup Method";
[0056] The bonding strength at 25°C was measured by bonding a silicon chip (chip size: 0.7mm×0.7mm×0.3mm) to a silver-plated cell. The test was based on MIL-STD-883.
[0057] The test method of volume resistivity refers to ASTM-D2739-97;
[0058] The storage modulus test at 25°C is based on ASTM D5026;
[0059] The PCT 48h aging conditions of battery components refer to JESD22-A102;
[0060] The EL test of the aged components is based on "IEC / TS 60904-13-2018 Photovoltaic Modules Part 13: Electroluminescence of Photovoltaic Modules".
[0061] The test results are as follows:
[0062]
[0063]
[0064] From the density and volume resistivity test results, it can be seen that the density of the conductive adhesive in Examples 1-3 is significantly lower than that of the ordinary conductive adhesive in Comparative Examples 1-2 due to the use of silver-coated plastic particles. In the sizing process of the shingled conductive adhesive, under the condition of the same volume of adhesive, the single-point weight of the low-density conductive adhesive is only 5mg to 6mg, which is more than 30% lighter than the weight of ordinary conductive adhesive, effectively reducing production costs and increasing market competitiveness. At the same time, the weight of the component can also be reduced, which is very beneficial for installation on roofs, car roofs and some special occasions with limited load-bearing capacity. Comparative Example 1 uses a large amount of silver powder, and the density is as high as 3.4g / cm 3 Although the volume resistivity is lower than that of Examples 1-3, the increase of pure silver powder also leads to a significant increase in cost. Although thin flake light silver powder is used as filler in Comparative Example 2 to reduce the amount of silver powder, the density still reaches 2.4g / cm 3 The contribution to cost reduction is limited, and the volume resistivity is higher than that of Examples 1-3 in which silver-coated plastic particles are added, which is not conducive to the current transmission between battery cells.
[0065] Considering the application scenario of the shingled component with a curved structure, the present invention uses both silicone-modified flexible epoxy resin and silver-coated plastic particles to adjust the modulus and adhesion of the conductive adhesive. Due to the use of silicone-modified epoxy resin, the content of Si-O bonds and Si-C bonds in the cured molecular chain increases. Compared with the CO bonds and CC bonds in the traditional conductive adhesive system, the chemical bonds become longer, the molecular distance increases, the free volume becomes larger, and the flexibility becomes better; at the same time, the addition of plastic particles can hinder the expansion of cracks in the conductive adhesive on the one hand, and also have a toughening effect; on the other hand, because the silver-coated plastic particles are spherical and have a very narrow particle size distribution, after being dispersed in the resin, they are more orderly and uniform in the colloid than flaky and spherical silver powder particles, ensuring the uniformity of the thickness of the adhesive layer during lamination and curing, and improving the stability and consistency of the product performance after lamination. The synergistic effect of the two is conducive to improving the mechanical load and reliability of the component. In Comparative Example 3, no silicone-modified epoxy resin was used, which resulted in a significant increase in the modulus of the conductive adhesive, a larger curing shrinkage rate, and better conductivity. However, when subjected to PCT, the stress damage was increased, which ultimately led to the failure of the EL test. In addition, a specific proportion of curing agent can effectively reduce production energy consumption, improve production efficiency, and maintain the operating time required for continuous operation of the solar shingling process. Comparative Example 4 did not use the curing agent described in the present invention, which affected the synergistic effect of the curing process. In addition, the effective ingredients of the core-shell structure curing agent were relatively low, which in turn affected the curing rate and volume shrinkage, and further affected the modulus, adhesion, and conductivity. Under the combined effect of these factors, after undergoing PCT accelerated aging, the EL test showed failure before reaching 48 hours.
[0066] From the results of adhesion and modulus testing, the adhesion strength of Examples 1-3 is greater than 10MPa, and the storage modulus is less than 3000MPa, which is more in line with the application requirements of shingled flexible solar panels. The silver-coated plastic Ag-10-3 particles used in Example 3 have an average particle size of 9.05μm at D50, 10.1μm at D90, and 12.7μm at D100; the silver-coated plastic Ag-20-02 particles used have an average particle size of 19.3μm at D50, 22.5μm at D90, and 30.4μm at D100; these two types of silver-coated plastic particles (particle size distribution as shown in Figure 2) are used. Figure 2 and Figure 3 As shown in the figure, a conductive adhesive with lower density is obtained, which balances the various performance requirements such as cost and bonding strength. In comparison, in Comparative Example 1, pure silver powder is used, and the modulus is significantly higher. Although the bonding strength is also relatively high, it is difficult to maintain stable performance when undergoing high temperature and high pressure PCT test. Although the silver powder content is reduced in Comparative Example 2, the modulus is also reduced by adding flexible resin, but the bonding strength and conductivity are affected by the elongation of the molecular chain segments of the solidified material, the shrinkage is reduced, the volume of the colloid occupied by the conductive powder is limited, and the distance between the conductive powders is increased. Similarly, after experiencing PCT48h accelerated aging, the EL test failed.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A low-density conductive adhesive used in photovoltaic shingled modules, characterized in that: The composition comprises the following components in parts by weight: Epoxy resin A 10-20 parts; Epoxy resin B 5-15 parts; Epoxy resin C 3-10 parts; Curing agent D 0.1-2 parts; Curing agent E 0.1-2 parts; Curing agent F1 to 5 parts; 0.1-0.5 parts of coupling agent; Conductive filler G 40-70 parts.
2. The low-density conductive adhesive used for photovoltaic shingled components according to claim 1, characterized in that: The epoxy resin A is a multifunctional phenolic epoxy resin with a viscosity of 2500-6500 Pa·s at 25° C., an average functionality of 2.2, an epoxy equivalent of 172-179 g / eq, and a total chlorine content of <1000 ppm.
3. The low-density conductive adhesive used for photovoltaic shingled components according to claim 1, characterized in that: The epoxy resin B is a silicone modified epoxy resin with a viscosity of 30-60 Pa·s at 25°C, an epoxy equivalent of 750-900 g / eq, and a density of 0.99-1.05 g / cm at 23°C. 3 .
4. The low-density conductive adhesive used for photovoltaic shingled components according to claim 1, characterized in that: The epoxy resin C is a high-purity, low-viscosity, bifunctional non-crystalline epoxy resin with a viscosity of 2-3 Pa·s at 25° C., an epoxy equivalent of 160-170 g / eq, and a total chlorine content of less than 800 ppm.
5. The low-density conductive adhesive used for photovoltaic shingled components according to claim 1, characterized in that: The curing agent D is imidazole, a light yellow liquid, with a molecular weight of 163.22 and a purity of 98.0%.
6. The low-density conductive adhesive used for photovoltaic shingled components according to claim 1, characterized in that: The curing agent E is a latent curing agent with a core-shell structure, which is used in a ratio with bisphenol A epoxy. The gel time at 130°C is 1 minute, the gel time at 170°C is less than 1 minute, the average particle size is 2μm, the viscosity is 70-200Pa·s, and the total chlorine is less than 1000ppm.
7. The low-density conductive adhesive used for photovoltaic shingled components according to claim 1, characterized in that: The curing agent F is a white powder with an average particle size of 5 μm, a molecular weight of 188.23, and a melting point of 192-197°C.
8. The low-density conductive adhesive used for photovoltaic shingled components according to claim 1, characterized in that: The coupling agent is a silane coupling agent, a light yellow liquid, with a molecular weight of 236.4, a boiling point of 260-262°C, and a density of 1.07 g / cm 3 .
9. The low-density conductive adhesive used for photovoltaic shingled components according to claim 1, characterized in that: The conductive filler G is one or more of: silver; nickel; carbon; carbon black; graphite; graphene; copper; gold; platinum; aluminum; iron; zinc; cobalt; lead; tin alloy; silver-coated nickel; silver-coated copper; silver-coated graphite; silver-coated aluminum; silver-coated glass; silver-coated plastic; and nickel-coated graphite.
10. A low-density conductive adhesive for use in photovoltaic shingled modules according to any one of claims 1 to 9, characterized in that: Epoxy resin A, epoxy resin B, epoxy resin C, curing agent D, curing agent E, curing agent F, coupling agent, and conductive filler G are weighed according to the formula ratio and put into a planetary mixer for stirring, and then vacuum degassing and stirring are performed to finally obtain a low-density conductive adhesive.
Citation Information
Patent Citations
Medium-low temperature cured low-density conductive adhesive as well as preparation method and application thereof
CN118256182A